Repeat Ablation and Hospitalization Following Cryoballoon Ablation of Atrial Fibrillation at a Single Tertiary Medical Center. Issue 1 (1st January 2017) - East, Cara; Phan, Teresa; Filardo, Giovanni; Franklin, Jay; Donsky, Alan; Wheelan, Kevin R.; Kowal, Robert C.
Abstract : Cryoablation for atrial fibrillation (AF) has rapidly become a mainstream treatment for AF. In this report, 163 patients who had undergone a cryoablation procedure at one clinical center were contacted by telephone 33.1 ± 3.3 months after the procedure. All patients had received cryoablation of the pulmonary vein ostia, although concomitant procedures were performed at the same time in over 50% of the patients, including radiofrequency and/or cryoablation of other areas of the left atrium. Freedom from a repeat ablation procedure was 87%, while freedom from recurrent hospitalization for AF was 89%, as compared to previous reports of 65%. Of the 13 patients who had a repeat ablation procedure, only one was found to have a reconnection of pulmonary veins, while 4 were found to have atrial flutter. Cryoablation for AF produces a durable result in most patients out to 3 years with better outcomes than previously reported.